Laying performance, blood profiles, nutrient digestibility and inner organs traits of hens fed an insect meal from Hermetia illucens larvae - Bovera, Fulvia; Loponte, Rosa; Pero, Maria Elena; Cutrignelli, Monica Isabella; Calabrò, Serena; Musco, Nadia; Vassalotti, Giuseppe; Panettieri, Valentina; Lombardi, Pietro; Piccolo, Giovanni; Di Meo, Carmelo; Siddi, Giuliana; et al. (Research in Veterinary Science, 2018)
Given probable the increment in the nutritional needs of both humans and animals, animal production will have increased dramatically by 2050. Insect meals could be an alternative protein source for livestock, and they would also be able to reduce the environmental problems related to intensive animal production system. The aim of this study was to evaluate productive performance, blood analysis, nutrient digestibility, and changes in the internal organs of laying hens fed Hermetia illucens larvae meal (HI) at two different levels in substitution (25 or 50%) of soybean meal (SBM). A total of 162 Hy-line Brown hens (sixteen weeks old) were equally divided into three experimental groups and fed isoprotein and isoenergetic diets. Egg weight, feed intake, and feed conversion rate were not affected by the soybean meal substitution at both inclusion levels of insect meal. Egg mass was positively affected by the insect meal diets, as was the lay percentage, although only at the lowest inclusion level. Dry matter, organic matter, and crude protein digestibility coefficients were lower for the HI50 diet, probably due to the negative effect of chitin. A reduction in serum cholesterol and triglycerides was observed in both insect-meal fed groups, while serum globulin level increased only at the highest level of insect meal inclusion, and, consequently, the albumin to globulin ratio decreased. Overall, a protein replacement of 25% with an insect meal from Hermetia illucens larvae in the diet of laying hens seems to be more suitable and closer to the optimal level.
Keywords: Nutrients; zvířata; triglyceridy; dieta; Larva; Female; Diptera; Glycine max; Chickens; Nutritive Value; fyziologie výživy zvířat; larva; Animal Feed; krmivo pro zvířata; Animal Nutritional Physiological Phenomena; Animals; Diet; Triglycerides; ženské pohlaví; nutriční hodnota; kur domácí; živiny